(untitled) (REVISTA NODO, 2026)
Where does the political agency of migrant art reside? In contrast to analyses centered on testimony or representation, this article argues that its critical force is fundamentally methodological. Drawing on a framework that integrates border thinking (Mignolo) as an epistemology of exteriority, black feminist critique (Lorde, hooks) as a theory of the gaze, and the agency of matter (Bennett) as a political ontology, we argue that the migrant condition activates poetics of remaking: formal and material strategies that translate the experience of displacement into critical procedures. A comparative analysis of Zanele Muholi, Marta Palau, and Lara Ruiz identifies three such strategies: 1) sovereign self-inscription, which establishes the body as a counter-archive; 2) transcultural material synthesis, which ritualizes mourning in matter; and 3) relational cartography, which produces the common through co- creation. Beyond their diversity, these practices converge in deactivating the spectacular aesthetics of trauma through specialized material tactics—over- inscription, materialization, and repair—that constitute an immanent critique of the necropolitical regime of the border. The article’s main theoretical contribution is the concept of an “aesthetics of the commons”, defined here in critical dialogue with its conservative genealogy (Hardin, 1968), yet reappropriated from a decolonial and feminist perspective as a material performance of the common. This concept synthesizes the political imaginary prefigured by the work of the selected artists: a horizon in which the common is performed as a sovereign body, material memory, and shared ground. Thus, the article repositions the debate, demonstrating that political transformation in migrant art is not proclaimed, but enacted through making.